Approximation to the Dynamic Hypermedial Device modeling for the analysis of interactions - Rodríguez, Guillermo L. (2010)
The following research proposes a first approximation to the Dynamic Hypermedial Device modeling based on the analysis of interactions. In addition, the DEVS (Discrete EVents dynamic Systems) formalism is employed, which is particularly suitable for the modeling of discrete event systems with continuous time. In this sense, the descriptive model of the denominated "Hypermedial Package" is presented as a basic conceptual component of the DHD. Then, a functional example of basic analysis of the interactions implemented in the PowerDEVS environment is shown. The ultimate goal of this proposal is to provide a tool to assist in the quality analysis and evaluation of the interaction processes through the Information and Communication Technologies (ICT). Moreover, because of the current use of ICT in research, education, and in other fields, they may help in the responsible construction of a more equitable, pluralistic and open "Knowledge Society".